THE EFFECT OF ADDING MORINGA LEAF FLOUR (Moringa oleifera) TO FERMENTED PASTED FEED ON THE GROWTH AND SURVIVAL OF GURAMI FISH LARVAE (Osphronemus gouramy Lac.) - Ihsan Fadhillah; Netti Aryani; Sukendi Sukendi (Asian Journal of Aquatic Sciences, 2026)
The growth of gurami fish larvae (Osphronemus gouramy Lac.) is often hindered by a limited supply of natural feed such as silkworms. Fermented paste feed supplemented with moringa leaf meal (Moringa oleifera) is expected to serve as an alternative feed that can reduce dependence on silkworms. The objective of this study was to determine the effect of fermented paste feed supplemented with moringa leaf meal (MLM) on the growth and survival of gurami fish larvae. The study was conducted over 40 days using a completely randomized design (CRD) consisting of six treatments with three replicates: P1 (0 g/kg MLF), P2 (20 g/kg MLF), P3 (40 g/kg MLF), P4 (60 g/kg MLF), P5 (80 g/kg MLF), and P6 (Tubifex sp.). The results showed that the addition of moringa leaf flour had a significant effect (P < 0.05) on absolute weight gain, absolute length gain, specific growth rate, and survival rate of gurami fish larvae. The best results were obtained in treatment P4 (60 g/kg TDK), with an absolute weight gain of 0.37 g, an absolute length gain of 1.58 cm, a specific growth rate of 8.36%/day, and a survival rate of 88.87%. Water quality parameters during the study remained within the optimal range, with temperatures ranging from 26.1–27.9 °C, a pH of 6.6–7.1, and dissolved oxygen levels of 5.2–6.6 mg/L.